High-intensity focused ultrasound (HIFU) therapy for benign thyroid nodules: a 3-year retrospective multicenter follow-up study. (1st January 2020) - Monpeyssen, Hervé; Ben Hamou, Adrien; Hegedüs, Laszlo; Ghanassia, Édouard; Juttet, Pauline; Persichetti, Agnese; Bizzarri, Giancarlo; Bianchini, Antonio; Guglielmi, Rinaldo; Raggiunti, Bruno; Alamri, Ahmad; Machuron, François; et al.
Abstract: Background: Outcomes of high-intensity focused ultrasound (HIFU), as a non-surgical treatment option for benign symptomatic thyroid nodules, has mainly been based on single-center studies and short-term follow-up. Therefore, we assessed the safety, and long-term efficacy of HIFU in benign thyroid nodules among four centers with expertise in thyroid mini-invasive procedures. Patients and methods: Retrospective three year follow-up study in four European centers, treating solid benign thyroid nodules causing pressure symptoms and/or cosmetic concerns. Nodule volume reduction was assessed at 1, 3, 6, 12, 24, and 36 months post-treatment. Technical efficacy, defined as a volume reduction rate (VVR) >50% was evaluated at 6, 12, 24 and 36 months. Predictive factors of efficacy were assessed using logistic models. Complications and side effects were classified according to the Interventional Radiology Guidelines and changes in local symptoms were scored on a visual-analog scale. Results: Sixty-five patients (mean age 51.1 ± 14.0 years; 86.2% women) with a single thyroid nodule and a mean baseline nodule volume of 9.8 ± 10.3 mL were treated with a mean energy of 7.1 ± 3.1 kJ (range: 2.0 to 15.5 kJ). Median nodule volume reduction was 31.5% (IQR: −38.6% to −23.1%) at 12 months and 31.9% (IQR: −36.4% to −16.1%) at 36 months. Technical efficacy was obtained in 17.2% of cases at 6 months, 17.8% at 12 months, 3.4% at 24 months, and 7.4% at 36 months. The number of treated pixels and the mean energy delivered were positively correlated to VRR at 1, 6 and 12 months. The risk of treatment failure decreased by 4.3% for each additional unit of energy delivered. The procedure duration was inversely correlated with treatment failure (OR 1.043, 95% CI: 1.011–1.083; p = 0.014 ). Improvement of cervical pressure symptoms or cosmetic complaints were observed in less than 15% of the cases at 12, 24 and 36 months. Horner's syndrome occurred in one case (1.5%) and minor complications, not requiring treatment, in three (4.6%) patients. No change in thyroid function was registered. Conclusions: HIFU carried a low risk of complications. A single treatment resulted in a 30–35% thyroid nodule volume decrease within one year, reduction that remained stable for 2 years. Outcomes varied significantly between centers with different HIFU expertise. Focus on improved HIFU technology, adequate training, and appropriate selection of patients is needed to achieve efficacy comparable to other thermal ablation procedures.